Cardiovascular Disorders in Systemic Lupus Erythematosus - Manolis, Antonis A.; Manolis, Theodora A.; Manolis, Antonis S. (Current Vascular Pharmacology, 2025)
Systemic Lupus Erythematosus (SLE) is a chronic autoimmune disease with multiorgan and system involvement, including the Cardiovascular (CV) system. Cardiac involvement in these patients is frequent and most often asymptomatic, at least in the early stages. It includes accelerated atherosclerosis, premature Coronary Artery Disease (CAD), and a high risk of CV complications. The risk of developing CV Disease (CVD) in SLE is linked not only with classical CV risk factors but also with disease-specific factors, like the degree of activity, autoantibodies, organ damage, and type of therapy. Clinical presentation comprises several clinical manifestations ranging from angina to acute Myocardial Infarction (MI) and Sudden Cardiac Death (SCD). The leading cause of death in SLE patients is from CVD due to accelerated atherosclerosis, which often has a more rapid progression compared with the general population. The CV risk in SLE is greater when antiphospholipid antibodies are present. Regarding diagnosis, apart from relevant blood tests, the simplest and readily available diagnostic test, echocardiography, with its contemporary techniques that include global longitudinal strain, is needed to provide a more thorough cardiac evaluation and allow for early management. These aspects of the disease, together with issues regarding phenotypes, biomarkers, neonatal lupus, heart block, SLE-related CV ailments such as coronary artery disease (CAD), myocarditis, valvular heart disease, and the antiphospholipid syndrome, as well as diagnostic modalities, drug and interventional therapies, and current relevant guidelines are all thoroughly reviewed and discussed in this article.
Keywords: echocardiography